SK channel blockade reverses cognitive and motor deficits induced by nigrostriatal dopamine lesions in rats. (August 2014) - Chen, Lin; Deltheil, Thierry; Turle-Lorenzo, Nathalie; Liberge, Martine; Rosier, Corinne; Watabe, Isabelle; Sreng, Leam; Amalric, Marianne; Mourre, Christiane
Abstract Parkinson's disease has traditionally been viewed as a motor disorder caused by the loss of dopamine (DA) neurons. However, emotional and cognitive syndromes can precede the onset of the motor deficits and provide an opportunity for therapeutic intervention. Potassium channels have recently emerged as potential new targets in the treatment of Parkinson's disease. The selective blockade of small conductance calcium-activated K+ channels (SK channels) by apamin is known to increase burst firing in midbrain DA neurons and therefore DA release. We thus investigated the effects of systemic administration of apamin on the motor, cognitive deficits and anxiety present after bilateral nigrostriatal 6-hydroxydopamine (6-OHDA) lesions in rats. Apamin administration (0.1 or 0.3 mg/kg i.p.) counteracted the depression, anxiety-like behaviors evaluated on sucrose consumption and in the elevated plus maze, social recognition and spatial memory deficits produced by partial 6-OHDA lesions. Apamin also reduced asymmetric motor deficits on circling behavior and postural adjustments in the unilateral extensive 6-OHDA model. The partial 6-OHDA lesions (56% striatal DA depletion) produced 20% decrease of iodinated apamin binding sites in the substantia nigra pars compacta in correlation with the loss of tyrosine hydroxylase positive cells, without modifying apamin binding in brain regions receiving DAergic innervation. Striatal extracellular levels of DA, not detectable after 6-OHDA lesions, were enhanced by apamin treatment as measured by in vivo microdialysis. These results indicate that blocking SK channels may reinstate minimal DA activity in the striatum to alleviate the non-motor symptoms induced by partial striatal DA lesions.